El futuro de la diplomacia pública: implicaciones para México - J. Cull, Nicholas (Revista Mexicana de Política Exterior, 2022)
Public diplomacy is constantly evolving and its study has become more complex in recent years. Nicholas Cull analyzes major trends in the practice of public diplomacy around the world, its progress, and some possible directions it may take in the future, as practiced by Mexico and other middle powers. According to the author, in the interests of building a better reputation abroad, Mexico could make more sophisticated use of the tools of public diplomacy and come up with original practices in keeping with its position in the world and diplomatic traditions. Specifically, and provided they are used appropriately, the signification and symbolization tools of modern-day digital communications media could benefit Mexico, given that these are capable of reaching audiences and influencing not just their consumer habits, but ways of creating identity in today’s global society.